Nutritional evaluation of some potential wild edible plants of North Eastern region of India - Talang, Hammylliende; Yanthan, Aabon; Rathi, Ranbir Singh; Pradheep, Kanakasabapathi; Longkumer, Soyimchiten; Imsong, Bendangla; Singh, Laishram Hemanta; Assumi, Ruth S.; Devi, M. Bilashini; Vanlalruati,; Kumar, Ashok; Ahlawat, Sudhir Pal; et al. (Frontiers in Nutrition, 2023)
India's north-eastern hill region (NEH) is one of the biodiversity hotspots, inhabited by several tribal communities still maintaining their traditional food habits. Much of their food resources are drawn from wild sources. Fourteen species of wild edible plants of high ethnic importance were collected from remote localities of Nagaland and Meghalaya states of the NEH region of India for nutritional profiling. Nutritional profiling of leaves of six species comprising Gynura cusimbua, Garcinia cowa, Herpetospermum operculatum, Plukenetia corniculata, Trichodesma khasianum, and Elatostemma sessile is conducted first time under present study. Samples were analyzed as per AOAC and standard methods for proximate composition. The range of variation in proximate composition was observed for moisture (72-92%), protein (1.71% - 6.66%), fat (0.22% - 1.36%), dietary fibre (5.16% - 14.58%), sugar (0.30% - 3.41%) and starch (0.07% - 2.14%). The highest protein content (6.66%) was recorded in Herpetospermum operculatum, followed by Trichodesma khasianum (5.89%) and Plukenetia corniculata (5.27%). Incidentally, two of these also have high iron (>7.0mg/100g) and high zinc (>2.0mg/100g) contents, except Trichodesma khasianum, which has low zinc content. High antioxidant activities in terms of GAE by the CUPRAC method ranged from 1.10 to 8.40 mg/100g, and by the FRAP method ranged from 0.10 to 1.9 mg/100g, while phenol content ranged between 0.30 and 6.00 mg/100g. These wild vegetables have high potential because of their nutritional properties and are fully capable of enhancing sustainability and improving ecosystem services. Efforts were also initiated to mainstream these resources, mainly for widening the food basket of native peoples.